Alcohol consumption and cognitive impairment in older men: A mendelian randomization study - Almeida, Osvaldo P. (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To determine whether alcohol consumption is causally associated with cognitive impairment in older men as predicted by mendelian randomization. METHODS: Retrospective analysis of a cohort study of 3,542 community-dwelling men aged 65 to 83 years followed for 6 years. Cognitive impairment was established by a Mini-Mental State Examination score of 23 or less. Participants provided detailed information about their use of alcohol during the preceding year and were classified as abstainers, occasional drinkers, and regular drinkers: mild (<15 drinks/wk), moderate (15–27 drinks/wk), heavy (28–34 drinks/wk), and abusers (≥35 drinks/wk). We genotyped the rs1229984 G→A variant of the alcohol dehydrogenase 1B (ADH1B) gene, which is associated with lower prevalence of alcohol abuse and dependence. Other measures included age, education, marital status, smoking and physical activity, body mass index, diabetes, hypertension, and cardiovascular diseases. RESULTS: At study entry, rs1229984 G→A polymorphism was associated with lower prevalence of regular use of alcohol and decreased consumption among regular users. Six years later, 502 men (14.2%) showed evidence of cognitive impairment. Abstainers and irregular drinkers had higher odds of cognitive impairment than regular drinkers (odds ratio [OR] = 1.23, 95% confidence interval [CI] = 1.00–1.51, after adjustment for other measured factors). The rs1229984 G→A polymorphism did not decrease the odds of cognitive impairment (AA/GG OR = 1.35, 95% CI = 0.29–6.27; GA/GG OR = 1.05, 95% CI = 0.71–1.55). CONCLUSIONS: Alcohol consumption, including heavy regular drinking and abuse, is not a direct cause of cognitive impairment in later life. Our results are consistent with the possibility, but do not prove, that regular moderate drinking decreases the risk of cognitive impairment in older men.